2021
DOI: 10.1186/s12986-021-00581-0
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise promotes the functions of brown adipose tissue in obese mice via a mechanism involving COX2 in the VEGF signaling pathway

Abstract: Background High-fat diet (HFD)-induced obesity causes immune cells to infiltrate adipose tissue, leading to chronic inflammation and metabolic syndrome. Brown adipose tissue (BAT) can dissipate the energy produced by lipid oxidation as heat, thereby counteracting obesity. Aerobic exercise activates BAT, but the specific underlying mechanism is still unclear. Methods Male C57BL/6 J mice were divided into a normal diet control group (NC group) and HF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…There were no significant differences in body length, Lee's index or muscle content between the two groups, but the fat content in the NC group was significantly higher than that in the NE group. Hence, exercise can reduce fat accumulation, which is consistent with previous research results (Fu et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…There were no significant differences in body length, Lee's index or muscle content between the two groups, but the fat content in the NC group was significantly higher than that in the NE group. Hence, exercise can reduce fat accumulation, which is consistent with previous research results (Fu et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Beige adipose tissue is inducible and is recruited in response to beta adrenergic stimulation. Diet-induced obesity reduces the relative amount of BAT and aerobic exercise has been shown to reverse this effect and improve metabolic health ( Fu et al, 2021 ). We are gaining a better appreciation of the complexity of adipose tissue physiology and the external factors that can affect it, such as exercise.…”
Section: Remodeling Of Adipose Tissue With Exercisementioning
confidence: 99%
“…In comparison to WAT, less is known about the effects of exercise on angiogenesis in BAT. One study found that exercise in obese mice resulted in an increased expression of vascular endothelial growth factor A (VEGFA) and increased BAT mass relative to sedentary groups ( Fu et al, 2021 ). In contrast, another study found that angiogenic gene expression increased in WAT, but was unchanged in BAT ( Lee, 2018 ).…”
Section: Remodeling Of Adipose Tissue With Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…Another study on diet-induced obesity showed significant alterations of BAT molecular networks associated with immune cell trafficking, lipid metabolism and connective tissue development after 24 weeks of diet consumption [35]. High fat diet-induced obesity resulted in reduction of UCP1 levels and overexpression of proinflammatory genes; while aerobic exercise led to the growth of BAT and the upregulation of anti-inflammatory genes in obese mice via cyclooxygenase 2 in the VEGF pathway [36]. Another model of diet-induced obesity in rats established development of BAT fibrosis and modulation of this parameter by intermittent food restriction [37].…”
Section: Fig 4 Brown Adipose Tissue Fibrosis Level and Tissue Leukocyte Infiltrationmentioning
confidence: 99%